Motion Detection and Base Isolation System for Earthquake-Resistant Relief Structures: Application of Biomimetics - Khamidi, M. Faris (2012)
The conceptual design of a motion detection and base isolation system for earthquake-resistant relief structures is presented. The design process, which applies principles of biomimetics, is inspired by the motion detection ability of birds and fishes and shock isolation ability of woodpeckers’ skulls. Concrete blocks with and without base isolators were subjected to shake table tests to evaluate the efficiency of the base isolation system. Results revealed that the base isolation system reduces horizontal acceleration of concrete blocks by approximately 82.00 ± 2.0%.